Variation in morphological and wood cell traits in coppice stems of Populus nigra L. and Salix alba L. - Keleş, Seray Özden (Czech Academy of Agricultural Sciences, 2021)
Coppice management is an ecologically important silvicultural practice to provide the quicker and higher potential of wood biomass production for industrial demands. Understanding morphological and anatomical responses of coppiced trees could help to determine the quantity and quality of wood and thus provide better management of coppiced tree plantations for short-time biomass production. However, there is a little investigation in morphological and anatomical adaptation in different fast-growing tree species. The present study, therefore, studied how morphology and anatomy vary between two fast-growing coppices of Populus nigra L. (black poplar) and Salix alba L. (white willow). Each coppiced tree was grown in a similar habitat and was at a similar age. However, each coppiced tree showed different morphological and anatomical plasticity in their stems in response to environmental factors. Poplar coppices showed better anatomical properties due to greater vessel diameter, fibre length, fibre width, fibre wall thickness, and ray height; however willow coppices had better morphological plasticity which had higher average stem height and ring width. The results suggest that willow coppices had the greater height growth potential even at 2 years of age than poplar coppices.
Keywords: wood cell anatomy; plant morphology; coppicing; Forestry; SD1-669.5; fast-growing species; 15. Life on land; 7. Clean energy